Thelephora dominicana (Agaricomycetes, Fungi), a new record for Mexico - Uitzil-Colli, Michael Oswaldo; Pinzón, Juan P.; Guzmán-Dávalos, Laura (Instituto de Ecología, A.C., 2020)
Background and Aims: The genus Thelephora belongs to Thelephoraceae, Thelephorales, Agaricomycetes, Basidiomycota, and corresponds to ectomycorrhizal macrofungi, with at least 50 species known around the world. Of these, 28 are found in tropical and subtropical ecosystems. Nevertheless, it is considered they are poorly known in the tropics. Therefore, the objective of this work was to contribute to the knowledge of tropical thelephoraceous fungi present in an area relatively unexplored in Mexico from the mycological point of view, such as the Yucatán state. Methods: Collections were made in a subdeciduous seasonal dry forest in the south of the Yucatán state, in Tekax municipality, during the rainy season of August-December 2017 and June-August 2018. All the material was examined using macromorphological data from fresh specimens, and micromorphologically by basidiomata sections observed with the optical microscope. The specimens are deposited in the herbaria IBUG and UADY. Key results: Thelephora dominicana was only known from Dominican Republic, hence this record increases its distribution range. Moreover, we report its potential association with species of Fabaceae and Polygonaceae families, such as Coccoloba spp. and Gymnopodium floribundum. In Mexico, only nine species were previously reported in Thelephora, T. dominicana being the tenth one and the seventh for the Mexican Neotropical region. From the Yucatán peninsula, T. cervicornis was the only known species of this genus, thus this is the second one from this area. Conclusions: This is the first report of T. dominicana for Mexico and the second time worldwide.